Real-time image matching for navigation system based on genetic algorithm - LENG Xue-fei1; LIU Jian-ye2; XIONG Zhi2 (Tongxin xuebao)
In order to meet requirement that scene matching aided navigation system must get aircraft position error real-timely, an image matching algorithm based on genetic algorithm and weighted Hausdorff distance was proposed. In general, the global search in conventional image matching is highly time consuming task. For the non-ergodic search characteristic of genetic algorithm was utilized, the global approximate optimum solution was approached rapidly. Therefore the rapidity of matching search can be improved by our algorithm. Moreover, the weighted Hausdorff distance algorithm based on bifurcations extraction and the corresponding weight formula was proposed. The calculation of matching search can be reduced and the accuracy of matching results can be improved by using the weighted Hausdorff distance as the fitness function of genetic algorithm. Simulation results show that, the proposed image matching algo- rithm combined with genetic algorithm and weighted Hausdorff distance can satisfy the real-time and accuracy demands of the scene aided navigation system.